CRISPR/Cas9 genome editing of CLU to examine clusterin's contribution to neurodegeneration and Alzheimer's disease: Molecular and cell biology/neurodegeneration and neuroprotection. (7th December 2020) - Foster, Evangeline M.; Ribe, Elena M.; Robbins, Jacqueline; Hublitz, Philip; Pangalos, Menelas; Buckley, Noel; Lovestone, Simon; Neuroscience, Translational; Research, Dementia
Abstract: Background: Traditionally, clusterin is referred to as a secreted protein however, more recent evidence indicates clusterin may exist intracellularly where it may have a pro‐apoptotic role. Previously, our lab observed altered clusterin trafficking in rodent neurons in response to amyloid‐β suggesting it may be a key factor in neurodegeneration. We aim to use CRISPR/Cas9 in human iPSCs to explore the contribution that clusterin plays in cellular vulnerability to amyloid‐β. Method: We aim to remove exon 2 from CLU since this exon contains the ER‐signal peptide thought to be required for secretion of clusterin protein. So far, we have generated heterozygous exon 2 knockout iPSCs (exon 2+/‐) which have been differentiated into cortical neurons and astrocytes. Clusterin gene and protein expression has been characterised in these iPSCs compared to control iPSCs. Response of control and exon 2+/‐ neurons and astrocytes to amyloid‐β treatment has also been explored. Result: Surprisingly, exon 2+/‐ iPSCs express significantly less intracellular clusterin than control iPSCs. Secreted clusterin expression is unaltered by the edit achieved but glycosylation state is altered. We build on previous findings in rodent neurons, showing that clusterin trafficking is also altered by amyloid‐β in both control iPSC‐neurons and iPSC‐astrocytes. This response is observed in exon 2+/‐ neurons but is absent in exon 2+/‐ astrocytes. Divergence in gene expression changes of DKK1‐signature genes is observed. Here, we describe differences in both gene and protein expression changes in response to amyloid‐β treatment in control and exon 2+/‐ cells. Conclusion: Currently, we are exploring whether differences observed in neuronal and astrocytic responses of exon 2+/‐ cells convey protection or vulnerability to amyloid‐β induced toxicity. To do so, we are using imaging techniques to quantify changes in cell death and neurite projections for both genotypes in response to treatment.